The Agricultural Act of 2014: land retirement programs, the Conservation Reserve Program (CRP) - Seidl, Andrew F., author; Villar, Daniel, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2014)
The Conservation Reserve Program is a voluntary land conservation program established in 1985. Its long term goal is to improve water quality, prevent soil erosion, and reduce loss of wildlife habitat through the removal of environmentally sensitive lands from agricultural production. Contracts through the Farm Service Administration (FSA) provide yearly rental payments to farmers who enroll in the program. The types of land sought out by CRP include "agricultural land prone to erosion, pasture or agricultural land that borders river or stream banks, or field magins" (USDA FSA, 2014). These contracts are ten to fifteen years in length and ensure improvements in environmental health and quality through the conversion of agricultural land back to natural or semi-natural vegetative cover. While under contract farmers are unable to respond to higher crop prices by replanting enrolled land, farmers who are not enrolled in the program benefit from the higher crop prices. In this way the CRP is both a land retirement program and supply control program (Hicks, 2008). Practices including riparian buffers, field windbreaks, filter strips, and wetland restoration encourage reduce run-off, provide wildlife habitat and help to preserve groundwater quality. Cost-shares are available to help pay for proposed conservation practices; these are made in addition to the annual rental payments. Overall, the program leads to an improvement in local environmental conditions while providing annual rental payments to farmers for providing these benefits.
June 2014.
Keywords: 2014 Farm Bill; Grassland Reserve Program (GRP)